Appraisal of the diagnostic procedures of acute pancreatitis in the guidelines - Yi, Ke-Qian (Syst Rev, 2021)
OBJECTIVES: The purpose of this study was to comprehensively assess the heterogeneity of procedures in the diagnostic guidelines for acute pancreatitis and to identify gaps limiting knowledge in diagnosing this disease. METHODS: A systematic search of a number of databases was performed to determine the guidelines for the diagnosis of acute pancreatitis in patients with severe pancreatitis. The guidelines for the diagnosis of severe pancreatitis were evaluated by AGREE II. The Measurement Scale of Rate of Agreement (MSRA) was used to assess the guidelines (2015–2020) and extract evidence supporting these recommendations for analysis. RESULTS: Seven diagnostic guidelines for acute pancreatitis were included. Only the 2019 WSES Guidelines for the Management of Severe Acute Pancreatitis and the Japanese Guidelines for the Management of Acute Pancreatitis: Japanese Guidelines 2015 had a total score of more than 60%, which is worthy of clinical recommendation. The average scores of the Scope and Purpose domain and the Clarity and Expression domain were the highest at 71.62% and 75.59%, respectively, while the average score of the Applicability area was the lowest at 16.67%. The included guidelines were further analyzed to determine the heterogeneity of the diagnosis of acute pancreatitis. The main reasons for the heterogeneity were the citation of low-quality evidence, the presence of far too many indicators for the classification of acute pancreatitis, unclear depictions of the standard, and poorly comprehensive recommendations for the diagnosis of the aetiology in the primary diagnosis of acute pancreatitis, the severity classification, the aetiological diagnosis, and the diagnosis of comorbidities. CONCLUSIONS: The quality of different diagnostic guidelines for severe pancreatitis is uneven. The recommendations are largely based on low-quality evidence, and the guidelines still have much room for improvement to reach a high level of quality. The diagnostic procedures for acute pancreatitis vary widely in different guidelines. There are large differences between them, and resolving the abovementioned reasons would be a very wise choice for guideline developers to revise and upgrade the guidelines in the future. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13643-020-01559-4.